2017
DOI: 10.1186/s13045-016-0384-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of fruquintinib in patients with previously treated metastatic colorectal cancer: a phase Ib study and a randomized double-blind phase II study

Abstract: BackgroundTo assess the efficacy and safety of fruquintinib, a vascular endothelial growth factor receptor (VEGFR) inhibitor, in metastatic colorectal cancer (mCRC) patients.MethodsA phase Ib open-label study and phase II randomized, placebo-controlled trial compared the efficacy of fruquintinib plus best supportive care (BSC) with placebo plus BSC in mCRC patients with ≥2 lines of prior therapies. The primary endpoint was progression-free survival (PFS).ResultsIn the phase Ib study, 42 patients took fruquinti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 20 publications
(25 reference statements)
2
45
2
Order By: Relevance
“…Furthermore, several small-molecule protein kinase inhibitors (PKI) targeting various kinases, including VEGFR3, are now available and some of them have been approved for the treatment of colorectal cancer. For example regorafenib (43,44), nintedanib (45), fruquintinib (46) and famitinib (47) progressed to phase II and III clinical trial, showing benefit without significant toxicity. These clinical data indicate that blocking VEGFR3 could provide a safe therapeutic approach also in nonmetastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several small-molecule protein kinase inhibitors (PKI) targeting various kinases, including VEGFR3, are now available and some of them have been approved for the treatment of colorectal cancer. For example regorafenib (43,44), nintedanib (45), fruquintinib (46) and famitinib (47) progressed to phase II and III clinical trial, showing benefit without significant toxicity. These clinical data indicate that blocking VEGFR3 could provide a safe therapeutic approach also in nonmetastatic colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…With new breakthroughs achieved in precision medical treatment, the prognosis can be further improved by chemotherapy combined with targeted therapy, such as bevacizumab plus chemotherapy in right-sided colon cancer, [ 61 ] vemurafenib, [ 50 ] fruquintinib. [ 49 ] Meanwhile, immunization therapy is expected to make great strides in treatment of CRC, such as anti-programmed death 1(PD-1) antibody and cytotoxic T-lymphocyte antigen 4 (CTLA-4) immunotherapy for advanced colorectal cancer. [ 57 , 62 ]…”
Section: Discussionmentioning
confidence: 99%
“…Several trials have compared the safety and efficacy of fruquintinib in mCRC patients. [ 49 ] In the phase Ib study, the median PFS was 5.8 months, and the median OS was 8.88 months. In the phase II study, the median PFS was 4.73 months in the fruquintinib group versus 0.99 months in the placebo group ( P < .001)…”
Section: The Current Status Of Treatment In Chinamentioning
confidence: 99%
“…Regorafenib has been approved to treat mCRC based on the results of two phase III studies CORRECT [ 10 ] and CONCUR [ 11 ]. Another clinical study involving fruquintinib also demonstrated promising anticancer effect on mCRC [ 12 ].…”
Section: Introductionmentioning
confidence: 99%